Study on the adsorption process of a semi-flexible polymer onto homogeneous attractive surfaces. (20th May 2019) - Yang, Xiao; Yang, Qing-Hui; Fu, Yu; Wu, Fan; Huang, Jian-Hua; Luo, Meng-Bo
Abstract: The dynamic adsorption process of a semi-flexible polymer onto homogeneous attractive surfaces is studied using dynamic Monte Carlo simulations. The adsorption time increases linearly with the bending rigidity, but it tends to be less dependent on the bending rigidity at large polymer-surface attraction strength, indicating that the semi-flexible polymer is softened by surface attraction during the adsorption process. The scaling relation between the adsorption time and polymer length is also studied, and different scaling exponents are found for rigid polymer and for flexible one. The adsorption time is influenced significantly by non-adsorbed monomers as they remain their original positions at time less than the adsorption time, that changes the relation between the adsorption time and the polymer-surface attraction strength. The semi-flexible polymer is finally adsorbed on the surface at about four times the adsorption time. Graphical abstract: Image 10 Highlights: Adsorption time is dependent on polymer rigidity and surface attraction strength. Adsorption time increases in different ways for rigid and flexible polymers. Adsorption time is influenced significantly by non-adsorbed monomers. Adsorption of semi-flexible polymer can be divided into two steps.